Effect of trust and integrity on the community happiness: performance as moderating role - Ahmad, Abd Rahman; Al Junaibi, Tareq Jumuaa; Adi, Nazir; Habibullah, Muzafar Shah; Mustafa, Hasri; Mahomed, Anuar Shah Bali; Talkah, Abu; Muharsono; Syahrul Reza; Hartono (Oxbridge Publishing House, 2022)
In the United Arab Emirates (UAE), the community police have been tasked with fostering community development. This study, conducted in the district of Baniyas in Al Shamkhah, explores the links between the constructs of integrity, trust, and community satisfaction, with performance serving as the moderator in the setting of the UAE. A quantitative research design built on a pragmatic approach was adopted. The complicated correlations between the constructs were estimated using descriptive statistics and partial least squares structural equation modeling (PLS-SEM) to answer the research questions. Integrity and trust, essential for effective community policing, were found to have a significant association with community happiness. Performance's moderating influence is on the link between integrity and community happiness. Thus, the trust serves as a predictor of happiness. The findings demonstrated that the policy feedback theory (PFT), legitimacy theory, and conceptual model given in this study provide explanatory aspects for community happiness and policing and explain the effect of police integrity and trust on community happiness. Future research should include additional constructs and variables, investigate community police officers' perceptions of community happiness, and measure the interrelationship between constructs to manipulate and strengthen the applicability of the theoretical model proposed in this study.